Analisis Strategi Program Nurul Falah Dakwah Dalam Menarik Calon Donatur - Putri, Hefi Alifia (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2024)
Non-profit institutions, especially those operating in the social sector and community empowerment, must continue to innovate to maintain the sustainability of their programs and benefits for the community. This continuous innovation helps institutions remain existing, relevant and impactful in society. In running programs consistently, non-profit institutions rely heavily on donor support to ensure the smooth running of each program. With this research, it is hoped that we can explore effective and efficient strategies in attracting donor interest and maintaining sustainable support for Nurul Falah's programs. By understanding what factors influence a donor's decision to donate, this institution can develop a more targeted strategy. This research will also explore how strong and sustainable relationships can be built with donors, so that they continue to feel compelled to support the da'wah program run by Nurul Falah. The method used in this research is a qualitative method because the researcher assumes that with qualitative research the researcher can find out the characteristics or object in depth and systematically, apart from that, qualitative research itself can help explore the perceptions, motivations and perception of the research object directly. LAZIS Nurul Falah Surabaya was chosen as the object because LAZIS Nurul Falah is one of the institutions that has interesting programs that are in accordance with the research carried out. Through the approach that has been taken, NF Dakwah has succeeded in building strong relationships with donors, providing real positive impacts, and creating sustainable support for its programs.